2022
DOI: 10.1257/pol.20200143
|View full text |Cite
|
Sign up to set email alerts
|

Removing Welfare Traps: Employment Responses in the Finnish Basic Income Experiment

Abstract: This paper provides evidence that replacing minimum unemployment benefits with a basic income of equal size has minor employment effects at best. We examine an experiment in Finland in which 2,000 benefit recipients were randomized to receive a monthly basic income. The experiment lowered participation tax rates by 23  percentage points for full-time employment. Despite the considerable increase in work incentives, days in employment remained statistically unchanged in the first year of the experiment. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…When the long-awaited results from the two-year Finnish basic income experiment were finally released in May 2019, almost 18 months after the experiment had been concluded, the verdict was that there was very little difference in employment or earned income between the experiment and control groups (Kangas et al, 2020). The average number of days of employment between November 2017 and October 2018 was 78 for the basic income group, while the corresponding figure for the control group was 73 (Verho et al, 2022). Over the first year of the experiment, there was no difference between the groups.…”
Section: Interpretation Of the Experiments Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…When the long-awaited results from the two-year Finnish basic income experiment were finally released in May 2019, almost 18 months after the experiment had been concluded, the verdict was that there was very little difference in employment or earned income between the experiment and control groups (Kangas et al, 2020). The average number of days of employment between November 2017 and October 2018 was 78 for the basic income group, while the corresponding figure for the control group was 73 (Verho et al, 2022). Over the first year of the experiment, there was no difference between the groups.…”
Section: Interpretation Of the Experiments Resultsmentioning
confidence: 92%
“…More surprisingly, the results from the final Finnish basic income experiment report revealed that many members of the basic income group did not want to abandon employment services and active labour market policy measures (Verho et al, 2022). They were in no way obliged to register with the employment office, but a great majority of them still decided to do so.…”
Section: Interpretation Of the Experiments Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This resulted in a substantial increase in work incentives, which was expected to improve employment among basic income recipients. However, the evaluation of the experiment by Verho et al (2022) shows that no noticeable employment effects materialized. This paper describes the evolution of the Finnish basic income experiment from a political initiative to the actual experiment and its evaluation, the particular focus being on how different family types responded to the changes in their work incentives.…”
Section: Introductionmentioning
confidence: 93%